Degradação ambiental e desertificação no nordeste brasileiro: o contexto da bacia do rio Acaraú - Ceará - Nascimento, Flavio Rodrigues do (2006)
The present paper approaches desertification within the scope of environmental degradation, in its worldwide, regional and local scales. In this context, Brazilian Northeastern region, specially the Acarau River Basin (Ceara State), was conceived as a territorial unit of territorial management and planning, face natural resources degradation and desertification. The socio-environmental diagnosis which generated discussions here had as theoretical-methodological presuppositions the integrated geoenvironmental analysis, scaffolded by historical and conceptual issues on the desertification phenomenon. In this trajectory, Brazilian Northeast was considered in its environmental complexity, above all, in which refers to its semi-arid portion, being enhanced the National Program of Combat against Desertification and Mitigation of Droughts Effects (Programa Nacional de Combate à Desertificação e Mitigação aos Efeitos das Secas/PAN-BRASIL). The basin in study has the intermittent-seasonal feature and it is placed, specifically, in Center-North of Ceara, occupying a 14.560 Km2 area. About 71,7% of its territory belongs to a semi-arid domain, standing out, within geoenvironmental partitioning, the hinterlands as predominant landscapes. It presents unimportant economic development, with overlapping primary sector. In general, it presents rudimentary technology, which produces low incomes as well as drastic and alarming socio-environmental reflexes among the reigning poverty. This socioeconomic overview contributes to weaken environmental sustainability and it magnifies geoenvironmental vulnerability face the desertification. Desertification consists in an unfolding of environmental degradation, engaged to the historical process of basin`s occupation. It is a remarkable fact impressed on different landscapes under influences of space organizers, with reflexes on the conservation of renewable natural resources, specially, of soils and vegetations, in a conflicted relationship of society x nature. The study also stood out the engaged strategies of contest against desertification, by considering the capacity-support of environmental actives, where were considered, among other purposes, guidelines based on the purpose of geoenvironmental zoning.